2005
DOI: 10.2136/sssaj2004.0215
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Carbon Input, Aggregation, and Soil Organic Carbon Stabilization in Sustainable Cropping Systems

Abstract: One of our current challenges is to quantify the mechanisms, capacity, and longevity of C stabilization in agricultural lands. The objectives of this study were to evaluate the long‐term (10 yr) role of C input in soil organic carbon (SOC) sequestration and to identify underlying mechanisms of C stabilization in soils. Carbon input and SOC sequestration, as governed by crop management strategies, were assessed across 10 Mediterranean cropping systems. Empirically derived relationships between yield and abovegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
351
10
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 621 publications
(418 citation statements)
references
References 35 publications
56
351
10
1
Order By: Relevance
“…This indicated that smaller particles with greater surface area may be responsible for scavenging a sizable amount of C in micro aggregates. Kong et al, (2005) and Majumder et al, (2007) also reported similar results. However, there was a little influence of increasing C inputs was observed for C associated with aggregates of 250-1000 and < 53 µm size.…”
Section: Aggregate Associated Carbon Fractionssupporting
confidence: 67%
See 2 more Smart Citations
“…This indicated that smaller particles with greater surface area may be responsible for scavenging a sizable amount of C in micro aggregates. Kong et al, (2005) and Majumder et al, (2007) also reported similar results. However, there was a little influence of increasing C inputs was observed for C associated with aggregates of 250-1000 and < 53 µm size.…”
Section: Aggregate Associated Carbon Fractionssupporting
confidence: 67%
“…A higher surface area for smaller particles may be responsible for this. Christensen (1986) and Kong et al, (2005) also reported similar results. Gupta Choudhury (2011) and Datta (2016) also reported similar findings in Indian subcontinent.…”
Section: Aggregate Associated Carbon Fractionssupporting
confidence: 64%
See 1 more Smart Citation
“…Using the same source, the absence of some kind of N input in herbaceous systems was associated to a net emission of 0.48 Mg C per hectare. We considered that 8.5 % of straw C was incorporated into the soil at a 100-year time horizon using data from other studies under Mediterranean conditions (Alvaro-Fuentes and Paustian 2011; Kong et al 2005). Organic farms usually produce more weed biomass than conventional ones (Guzmán et al 2014).…”
Section: Carbon Sequestrationmentioning
confidence: 99%
“…Crop cultivation is known to adversely affect the distribution and stability of soil aggregates and reduces SOC stock in soils (Kong et al, 2005). The impacts of cultivation on C stock have commonly been observed to be restricted mostly to surface soils and/or to root zone depth (Paustian et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%